Dakwah Bil Lisan Melalui Media Sosial Pada Komunitas Hijrah Di Kota Solo - Muhammad Raqib; Ade Yuliar; Siti Nuraeni (Jurnal Dakwah dan Komunikasi, 2022)
The development of hijrah in Indonesia is increasingly widespread with the emergence of the phenomenon of hijrah communities. As is the case with the Yuk Ngaji Solo hijrah community, which conveys da'wah messages through social media, especially through Instagram. The da'wah method used is the oral bill method through the @yukngajisolo Instagram account in the form of lecture content by taking into account the conditions in the hijrah community. This study aims to determine the method of da'wah carried out through Instagram and to find out the changes for the congregation after listening to the study of da'wah through Instagram with live streaming. To get the answer, the researcher used qualitative research. Sources of data through observation, interviews and documentation. The validity test uses triangulation technique. The results showed that the da'wah bil oral method through the @yukngajisolo instagram account in the hijrah community in the city of Solo was using the lecture method which contained good advice using words that were easy to understand and spoke well with full courtesy, full of respect with using the ethical principles of touching words, namely qaulan baligha, qaulan ma'rufa, qaulan maysura and qaulan layyina).